The Implementation of Character Education Through Religious Activities in the School - Hasnadi Hasnadi; Cut Shella Mei Santi (IAIN Padangsidimpuan, 2021)
School is a strategic place to apply character education to students as the nation's next generation. The strategy in implementing character education in schools is through religious activities carried out in schools. This article aims to analyze and describe the planning, implementation and obstacles faced by schools in implementing character education through religious activities. This research is a qualitative research conducted in MIN 3 Aceh Barat. The research subjects were principals, supervisors, teachers, school committees and students. Data was collected through interviews, observation and documentation. Data analysis technique is done by data reduction, data display and conclusion drawing. The results showed that: (1) Planning activities carried out in each new school year by involving all school personnel, parents and school committees. Decision making is determined based on a joint decision through the stages of determining programs, costs required, program implementation plans, implementation and evaluation of religious activity programs. (2) The determined religious programs carried out on a scheduled and continuous basis until they become a habit. (3) Obstacles faced include: the dual role of teachers so that activities are not optimal, facilities for religious activities are not all adequate, the motivation of students varies in participating in religious activities at school, and parental support for activities at school is not optimal.